The role of teachers in fostering the practice of worship SMK Muhammadiyah 2 Blora - Munawar, Mohamad (2016)
ABSTRACT The purpose of this study was to determine: 1) Methods of coaching practice worship SMK Muhammadiyah 2 Blora; 2) The role of teachers in fostering the practice of worship SMK Muhammadiyah 2 Blora; and 3) the practice of worship SMK Muhammadiyah 2 Blora This type of research is qualitative research. The research object is class XI student of SMK Muhammadiyah 2 Blora with a focus on fostering the practice of worshiping the students, while the research subject is the principal, teachers PAI. Data collected by observation, interviews, questionnaires and documents. The validity of the data using the data triangulation, member check, preparation of data base, a test of credibility and preparation of evidence chain of research. Data analysis was performed using qualitative descriptive analysis reinforced with quantitative calculations. The results of this analysis concluded: 1) Methods of Islamic religious education teachers in fostering the practice of worshiping the students are classified into two theoretical and practical. In terms of theoretical done by providing instruction in accordance with the Shari'a, such as reading the Qur'an, prayer, and prayer. In terms of practice to provide guidance and oversight as read quran for students who can not read the Qur'an, provide guidance prayer practices, provide guidance memorizing letters and prayers everyday. Then the latter provide supervision to students. 2) The role of teachers in coaching practice of worship covers provide instruction, guidance and supervision. 3) Overall student worship practice that includes: reading the Qur'an, prayer, and pray fard prayers everyday in terms of intensity has been good, although there are still less than the maximum that is on the prayers habits at school and prayed. Psychomotor aspect of students with the indicator carry out religious activities in school practice has shown that a good percentage of the value, so that the study supports the theory that the Islamic religion is very concerned with the education of habit, by habituation that is expected of students to practice their religion in a sustainable manner (especially religious). students practice worship in schools. Keywords: coaching methods; practice of worship